2008
DOI: 10.1590/s0034-72802008000600003
|View full text |Cite
|
Sign up to set email alerts
|

Custo-efetividade dos análogos de prostaglandinas no Brasil

Abstract: RESUMOObjetivo:Avaliar a relação custo-efetividade dos análogos das prostaglandinas para o tratamento do glaucoma e da hipertensão ocular no estado de Minas Gerais, Brasil. Métodos: Este estudo transversal avaliou o custo (preço máximo ao consumidor) das diferentes apresentações dos análogos de prostaglandinas (bimatoprosta, latanoprosta, travoprosta) em relação à sua efetividade na redução da pressão intra-ocular. Para cada uma das medicações, calculou-se o custo mensal, anual e em 5 anos para se obter uma re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
(22 reference statements)
0
4
0
3
Order By: Relevance
“…In this study, they found that the bimatoprost would present the best cost-effectiveness, concluding that in addition to the traditional evaluations of safety and efficacy of medicines, the cost-effectiveness analysis should be considered to assist in individual and collective decision-making. 35 Other authors found similar results [36][37] In Brazil, bimatoprost was also the most costeffective in treatment as an isolated drug or in association with the timolol. [37][38] Yu et al compared trabeculectomy as the initial treatment versus the traditional treatment approach, starting with medications and developing for surgery as needed.…”
Section: Outcome Measures For Economic Evaluation In Glaucomamentioning
confidence: 68%
See 1 more Smart Citation
“…In this study, they found that the bimatoprost would present the best cost-effectiveness, concluding that in addition to the traditional evaluations of safety and efficacy of medicines, the cost-effectiveness analysis should be considered to assist in individual and collective decision-making. 35 Other authors found similar results [36][37] In Brazil, bimatoprost was also the most costeffective in treatment as an isolated drug or in association with the timolol. [37][38] Yu et al compared trabeculectomy as the initial treatment versus the traditional treatment approach, starting with medications and developing for surgery as needed.…”
Section: Outcome Measures For Economic Evaluation In Glaucomamentioning
confidence: 68%
“…35 Other authors found similar results [36][37] In Brazil, bimatoprost was also the most costeffective in treatment as an isolated drug or in association with the timolol. [37][38] Yu et al compared trabeculectomy as the initial treatment versus the traditional treatment approach, starting with medications and developing for surgery as needed. In a 4-year period, the initial therapy with trabeculectomy was more costeffective for patients with moderate to advanced glaucoma.…”
Section: Outcome Measures For Economic Evaluation In Glaucomamentioning
confidence: 68%
“…Neste estudo, a bimatoprosta foi superior à latanoprosta e à travoprosta. (11) Este mesmo resultado foi obtido por pesquisadores em outros locais do mundo. (12,13) No entanto, em grande parte dos casos, faz-se necessário a adição de uma segunda droga com o objetivo de se atingir a PIO-alvo.…”
Section: Discussionunclassified
“…No estudo de Guedes et al sobre a relação de custo-efetividade das prostaglandinas, observa-se que o volume do frasco tem uma grande influência no resultado de custo-efetividade (bimatoprosta em frascos de 5 ml é mais custo-efetiva que a bimatoprosta em frascos de 3 ml). (11) Outra razão importante é que o preço máximo ao consumidor (PMC) da associação BT é menor que das outras (R$ 83,07 versus R$ 126,03 para a associação LT e R$ 97,47 para a associação TT). A combinação dos fatores citados: conteúdo maior do frasco e PMC menor faz com que a associação BT tenha um menor custo diário, mensal, anual e em 5 anos.…”
Section: Discussionunclassified
“…In addition, there are indirect costs, such as the expenses with the caregiver for the visually impaired and with rehabilitation, disability to work, among others. (13) The objective of this study was to evaluate the intra and inter -examiner variation of the volume of drops dispensed from the bottles of lubricating eyedrops (artificial tears) from five manufacturers available in the Brazilian market.…”
Section: Determination Of the Standard Average Massmentioning
confidence: 99%